2011
DOI: 10.1029/2011jd016112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the aerosol forcing efficiency in the UV erythemal range at Granada, Spain

Abstract: [1] Atmospheric aerosols represent one of the most important components that attenuate solar radiation reaching the Earth's surface. The aerosol radiative forcing (ARF) at the surface is usually determined in the visible range of the solar spectrum. In contrast, there are few experimental works in the literature about the ARF in the ultraviolet (UV) region. Therefore, this paper focuses on quantifying the aerosol forcing efficiency in the UV erythemal range (AFE ery ), ARF per unit of aerosol optical depth (AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 57 publications
8
24
0
Order By: Relevance
“…In fact, the lowest values of daily ARF at TOA corresponded to the lowest monthly values of the single scattering albedo for those months (Valenzuela et al, 2012a). This result is in agreement with the works of Di Biagio et al (2009) and Antón et al (2011) who showed that the single scattering albedo has a large influence on the daily ARF. The small values of the forcing at TOA during those months and the corresponding high values at the surface mean that less solar energy reached the ground and more energy was absorbed by atmosphere.…”
Section: Annual Evolution Of Aerosol Radiative Forcingsupporting
confidence: 82%
“…In fact, the lowest values of daily ARF at TOA corresponded to the lowest monthly values of the single scattering albedo for those months (Valenzuela et al, 2012a). This result is in agreement with the works of Di Biagio et al (2009) and Antón et al (2011) who showed that the single scattering albedo has a large influence on the daily ARF. The small values of the forcing at TOA during those months and the corresponding high values at the surface mean that less solar energy reached the ground and more energy was absorbed by atmosphere.…”
Section: Annual Evolution Of Aerosol Radiative Forcingsupporting
confidence: 82%
“…7. Furthermore, the influence of mineral dust aerosol (with high aerosol optical depth) during these months also causes strong radiative effects, as was also reported by previous studies (e.g., Cachorro et al, 2008;Guerrero-Rascado et al, 2009;Antón et al, 2011;Román et al, 2013;García et al, 2014). In addition, the bimodality of the monthly AOD climatology mentioned in Section 4 has its impact on the radiative effects.…”
Section: Inter-annual and Intra-annual Evolution Of Aresupporting
confidence: 58%
“…The AFE is a function of the aerosol optical properties, where both the aerosol particle size distribution and absorptive properties play a key role (e.g., Antón et al, 2011). As we assumed a fixed value of SSA = 0.90 in the simulations with AOD 440 nm < 0.15 (see Table 2), the AFE is calculated only for those cases showing AOD 440 nm larger than 0.15.…”
Section: Aerosol Radiative Forcing Efficiency In Different Spectral Rmentioning
confidence: 99%
“…This will shine a new light on the influence of the aerosols on the UV radiation at Uccle. Antón et al (2011) already reported that it is hard to determine the effect of aerosols due to their temporal and spatial variability and the difficulties associated with their characterization.…”
Section: Seasonal Mlr Analysis Using Total Ozone Column Global Solarmentioning
confidence: 99%